2001
DOI: 10.1128/aac.45.1.196-202.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amoxicillin, Gentamicin, and Moxifloxacin on the Hemolytic Activity of Staphylococcus aureus In Vitro and In Vivo

Abstract: In Staphylococcus aureus infection hemolysis caused by the extracellular protein ␣-toxin encoded by hla is thought to contribute significantly to its multifactorial virulence. In vitro, subinhibitory concentrations of ␤-lactam antibiotics and fluoroquinolones increase the levels of hla and ␣-toxin expression, whereas aminoglycosides decrease the levels of hla and ␣-toxin expression. In the present study we investigated the effects of subinhibitory concentrations of amoxicillin, gentamicin, and moxifloxacin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 29 publications
0
36
0
3
Order By: Relevance
“…No significant expression of leukotoxins or regulatory factors was detected in the vitreous 1 h after the administration of the 20-mg/kg dose, either because of the low bacterial density or because of a potential reduction of the expression. Worlitzsch et al (46) reported a decrease of total hemolytic activity by S. aureus in infected rat pouches treated with MXF.…”
Section: Discussionmentioning
confidence: 99%
“…No significant expression of leukotoxins or regulatory factors was detected in the vitreous 1 h after the administration of the 20-mg/kg dose, either because of the low bacterial density or because of a potential reduction of the expression. Worlitzsch et al (46) reported a decrease of total hemolytic activity by S. aureus in infected rat pouches treated with MXF.…”
Section: Discussionmentioning
confidence: 99%
“…Under reduced-aeration conditions, our data suggest that the posttranslational modification that blocks MgrA dimerization, combined with an increase in protease expression, contributed to norB derepression. Abscesses and the cystic fibrosis airway are environments that are both acidic and low in oxygen (pH is 5.5 in abscesses) (28,29), conditions that may result in additive effects on MgrA regulation and the expression of NorB and other effector proteins, the levels of which are under its control. Thus, understanding the mechanisms behind bacterial adaptation to stresses such as acidity or oxygen level may identify targets for interfering with bacterial fitness and resistance to antibiotics at sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that the expression of virulence genes in S. aureus is affected by subinhibitory concentrations of different antibiotics (Ohlsen et al, 1998;Worlitzsch et al, 2001;Nielsen et al, 2012). Knowledge of how pathogenic bacteria react in the presence of a subinhibitory concentration of AMPs is important information that to date has not been thoroughly investigated when evaluating the potential of peptides as drugs used in the inhibition of pathogenic bacteria.…”
Section: Fl9 Induces the Transcription Of Hla And Rna IIImentioning
confidence: 99%